PSYCHOLOGICAL CONTRACT IN IMPROVING HUMAN RESOURCES STRATEGY WITH ORGANIZATIONAL CULTURE AS A MEDIATOR VARIABLE - Sry Rosita; Edward Edward; Fitri Widiastuti (Management Department, Faculty of Economics and Business, Universitas Jambi, 2019)
The minimum criteria regarding the qualifications and competencies of lecturers in conducting education require psychological contracts, organizational culture and the strategy of Human Resources (HR) that are used as the basis for work relationships. The main objective of this research is to examine psychological contracts in improving HR strategies with organizational culture as a mediator variable. The method used in this research is kind of descriptive with a quantitative approach and use explanatory surveys. The research target was lecturers at several universities in Jambi Province. The data collection method used is by providing a structured questionnaire aimed at the sample respondents. The analysis tool used in this study is Partial Least Square (PLS) and the software used is smart-PLS. The research hypothesis provides strong support towards the view of psychological contracts has a positive and significant influence in improving HR strategies, psychological contracts have a positive and significant influence in improving HR strategies through organizational culture as a mediator variable.